A8.8 Controllable hydrogen sulfide donors and their anti-inflammatory potential in the murine macrophage cell line RAW264.7. (31st January 2014) - Kloesch, Burkhard; Becker, Tatjana; Zhao, Yu; Xian, Ming; Steiner, Guenter
Abstract : Background and Objectives: Hydrogen sulfide (H2 S) is a newly discovered gaseous signalling molecule like CO and NO and plays an important role in many physiological and/or pathological processes. Modulation of H2 S levels could have tremendous therapeutic value. However, the research on H2 S has been hindered by lacking controllable H2 S donors which could mimic the slow and continuous H2 S generation in vivo. In this study we report about the biological evaluation of a new class of H2 S donors releasing H2 S upon activation by cysteine or reduced glutathione (GSH). Material and Methods: The murine macrophage cell line RAW264.7 was preincubated for 1 hr with increasing concentrations (10 – 500 µM) of the H2 S donors termed 5a, 5b, 8a and 8l in the presence of 1 mM cysteine before the cells were stimulated for 24 hrs with LPS (100 ng/ml). Vice versa, macrophages were stimulated for 6 hrs with LPS and cells were post-treated with the compounds at the same concentrations plus cysteine. TNF-α and IL-6 levels were quantified by ELISAs. Nitrite as a marker for iNOS activation was monitored by a commercially available kit. Activation of the transcription factor NF-κB and modulation of mitogen activated protein kinases (MAPKs) such as p38 and ERK1/2 were analysed by Western blot. Results: The compounds 5a and 8a showed potent anti-inflammatory effects in RAW267.4 cells. TNF-α and IL-6 expression was effectively diminished even when the cells were post-treated with the compounds after LPS stimulation. In line with these results, nitrite production was also reduced demonstrating that these compounds also blocked activation of iNOS. In contrast to the compounds 5a and 8a, the inhibitory effects of 5b and 8l on TNF-α and IL-6 expression were much less pronounced. Conclusions: This study gives a first insight into the cellular mechanism of these new class of inducible H2 S-releasing compounds and suggest it as possible remedies for the treatment of chronic inflammatory diseases like RA.